Answer: hi your question is poorly written below is the correct question
answer :
a) y1 = Asint, y'1 = Acost , y"1 = -Asint
b) y2 = Bcost, y'2 = Bsint , y"2 = - Bcost
c) y = Asint + B cost satisfies the differential equation for any constant A and B
Explanation:
y" + y = 0
Proves
a) y1 = Asint, y'1 = Acost , y"1 = -Asint
b) y2 = Bcost, y'2 = Bsint , y"2 = - Bcost
c) y3 = y1 + y2 , y'3 = y'1 + y'2, y"3 = y"1 + y"2
∴ y"1 + y1 = -Asint + Asint
y"2 + y2 = -Bcost + Bcost
y"3 - y3 = y"1 + y"2 - ( y1 + y2 )
= y"1 - y1 + y"2 - y2
= -Asint - Asint + ( - Bcost - Bcost ) = 0
Hence we can conclude that y = Asint + B cost satisfies the equation for any constant A and B